PENGARUH TEMPERATUR TERHADAP HASIL UJI SEM AGLOMERASI CO-FIRING RDF MSW DAN BATUBARA PADA FLUIDIZED BED COMBUSTOR - Sebastian, Eli; Winaya, I Nyoman Suprapta; Astawa, Ketut; Pratama, I Putu Angga Yuda; Tenaya, I Gusti Ngurah Putu (Teknik Desain Mekanika; Vol 13 No 3 (2024): Juli 2024 : Teknik Desain Mekanika, 2024)
Abstract One way to convert waste into fuel is to convert it into RDF. The co-firing method is the combustion of two different types of fuel in a certain ratio. Co-firing can be used in fluidized bed combustion technology by using air to make the bed material have fluid-like properties, so that the combustion process becomes better. In this test, co-firing was used for combustion of 95% coal and 5% MSW RDF. To observe the agglomeration phenomenon, temperature variations of 750 °C, 850 °C, and 950 °C were used. The results show that temperature greatly influences the formation of agglomeration in the ash produced from the combustion of Fluidized Bed RDF MSW with coal. In the experiment with 750°C variation, the agglomerations formed were small and had a denser structure. In the 850°C and 950°C experiments, larger agglomerates were formed and the microstructure of the agglomerates looked like ash that melted and then solidified to form lumps. Keywords: Co-firing, Fluidized Bed Combustor, RDF MSW, Aglomeration